2014
DOI: 10.1155/2014/908476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surfactants on the Rate of Chemical Reactions

Abstract: Surfactants are self-assembled compounds that depend on their structure and electric charge can interact as monomer or micelle with other compounds (substrates). These interactions which may catalyze or inhibit the reaction rates are studied with pseudophase, cooperativity, and stoichiometric (classical) models. In this review, we discuss applying these models to study surfactant-substrate interactions and their effects on Diels-Alder, redox, photochemical, decomposition, enzymatic, isomerization, ligand excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 81 publications
0
50
0
Order By: Relevance
“…This increases the effective concentrations of the reactants as well as increases the collision probability giving rise to a higher reaction rate [38,39]. Interaction of SDS molecules with substrate malonic acid results in increasing the reaction rate or changing the yield of reaction and sometimes these surfactant molecules act as reactants [40]. The role of the surfactant in this case is to facilitate substrate solubilization and its close contact with the catalyst.…”
Section: Influence Of Sds On Reaction Ratementioning
confidence: 99%
“…This increases the effective concentrations of the reactants as well as increases the collision probability giving rise to a higher reaction rate [38,39]. Interaction of SDS molecules with substrate malonic acid results in increasing the reaction rate or changing the yield of reaction and sometimes these surfactant molecules act as reactants [40]. The role of the surfactant in this case is to facilitate substrate solubilization and its close contact with the catalyst.…”
Section: Influence Of Sds On Reaction Ratementioning
confidence: 99%
“…In addition to the interaction with substrate molecules, surfactants can sometimes form ion pairs with them. Non-ionic surfactants attack cationic crystal violet dye, and cause the formation of dye-surfactant ion pair 36 . The mechanism between crystal violet dye substrate and non-ionic surfactants may be characterised by the Piszkiewicz model with some modifications 35 .…”
Section: Effect Of Surfactant Concentration On Cpementioning
confidence: 99%
“…Tergitol NP-7 has lower volumes of preconcentration in comparison to Triton X-114. Because of the high solubility of solute, it is observed that the preconcentration factor decreases with an increase in surfactant concentration at constant operating temperature and dye concentration 36,37 .…”
Section: Preconcentration Factormentioning
confidence: 99%
“…It is observed that the rate constant increases in presence of [CTAB], SDS, and CHAPS. The alteration of electron transfer rate constant in the presence of SDS, CTAB, and CHAPS has been investigated at 303 K. The conclusion is that the micellar effects on the electron transfer rate constant can be explained by considering the micelles as a special background electrolyte with a high electric charge and a strong power of hydration [24].…”
Section: Rate Enhancement Effect By Ctabmentioning
confidence: 99%
“…Surfactants are amphiphilic organic compounds, containing both hydrophobic groups and hydrophilic groups. Thus, a surfactant molecule contains both a water insoluble and a water soluble component [24]. We have employed an approach to the determination of kinetic constants of metal mediated-micelle catalyzed oxidation of valeraldehyde that allows the identification of important mechanism and function of different surfactants on the reaction rates.…”
Section: Introductionmentioning
confidence: 99%